Love lost in translation : homosexuality and the Bible - Lings, K. Renato ([United States] : Trafford Pub, 2013)
Love lost in translation systematically examines the biblical stories and passages that are generally assumed to deal with, or comment on homoerotic relations; Noah and Ham, Sodom and Gomorrah, Leviticus 18:22, Deuteronomy 23:17-18, Judges 19, Romans 1: 26-27, and I Corinthians 6:9 K Renato Lings convincingly demonstrates that mistranslation of these texts into Greeek, LAtin and other languages occurred early, and that serious errors continue to be committed by translators today, this explains the painful controversy about same-sex relationships, which has rocked Christian churches for decades.
Contents: Creation, sex and knowing-- The language of sex-- To know in the biblical sense-- Noah's nakedness-- Consecrated-- With a male-- Sodom in the Bible-- Sodom yesterday-- Sodom today-- Translating Sodom-- The victim of Sodom-- The outrage at Gibeah-- Softies and male-liers-- Beyond nature-- Love lost in translation
Includes bibliographical references and indexes
Keywords: Homosexuality -- Biblical teaching; Homosexuality -- Religious aspects -- Christianity